Valores normativos para o teste de degrau incremental em adultos e idosos de ambos os sexos - Amaral, Daniel Pereira do (2019)
Background: The modified incremental step test (MIST) has been validated for patients with chronic obstructive pulmonary disease, and it determined similar physiological responses at the peak of exercise when compared to the cardiopulmonary exercise test. However, the interpretation of the MIST is difficult due to the absence of reference values. Objective: To establish a prediction equation for the MIST (number of steps) in adults and the elderly. Methods: 183 healthy subjects, divided into decades (18–28 yrs, 29–39 yrs, 40–49 yrs, 50–59 yrs, 60–69 yrs, and 70–83 yrs), underwent spirometry and two MIST (30 min apart). The MIST was performed on a platform (20cm high). It is an external-paced test starting with 10 steps/minute and an increase of one step every 30 sec up to the limit of tolerance. Five men and women were randomized to perform the MIST also in a platform 15cm and 25cm high (n =48). Results: The independent variables (age, body mass index, sex and delta of heart rate) were inserted in the multiple regression model determining the following reference equation: number of steps = 84.239 – (2.364 x age) + (77.111 x sex) + (3.409 x delta of heart rate), considering 1 for male and 0 for female (R² = 51%). Number of steps decreased according to the increase of age for both men (18-28 yrs: 507  204, 29-39 yrs:372166,40-49yrs:343142,50-59yrs:25670,60-69yrs:21689,and70-83yrs:16782)andwomen(18-28yrs:370126,29-39yrs:361193,40-49yrs:276124,50-59yrs:20660,60-69yrs:15552,70-83yrs:11939),withsignificant difference between earliest and oldest ages. The MIST was reproducible for all decades with intraclass correlation coefficients ranging from 0.75 to 0.94. Concerning different heights of steps (15 cm vs. 25 cm), a significant difference was found for four out of six decades (18-28 yrs, 29-39 yrs, 40-49 yrs, and 60-69 yrs). There weresignificantcorrelationsbetweenthenumberofstepsandage(r=-0.695),VO2(r= 0.880), sex (r = -0.373), height (r = 0.456), and BMI (r = -0.457). Conclusion: A reference equation has been established to predict the number of steps performed in the MIST which can be used to interpret the performance of this test in several health conditions.